Epistemologi sebagai Sumber Ilmu Pengetahuan dalam Perspektif Muhammad Abed al-Jabiri dan James Frederick Ferrier - Eva Sulastriyani (Gunung Djati Conference Series, 2023)
This study aims to discuss epistemology as a source of knowledge in the perspective of Muhammad Abed al-Jabiri and James Frederick Ferrier. This study uses a qualitative approach by applying a descriptive-analytical method. The material object of this research is epistemology as a source of knowledge, while the formal object of this research is the perspective of Muhammad Abed al-Jabiri and James Frederick Ferrier. The results and discussion in this study indicate that epistemology is a source of knowledge. In the Western world there are two sources, namely empiricism and rationalism. Whereas in Islamic epistemology there are three sources of knowledge, namely bayani, burhani, and irfani. In this study it was concluded that epistemology is a source of knowledge both in the West and in Islam. This research recommends Islamic studies institutions to further advance the mindset of society in a better direction in dealing with epistemological systems that can be applied to humans.